PENERAPAN PERENCANAAN STRATEGIS DALAM PENYUSUNAN PROGRAM PENDIDIKAN - Ampry, Evy Segarawati (Pascasarjana Universitas Negeri Makassar, 2013)
The Implementation of Strategic Plan in Formulating Education Program at Youth and Sports Education Office in Enrekang District. Where strategic planning in the preparation of educational programs according to the needs and potential of the region , support mechanisms and adequate organization, having professional and support data and relevant information. The aim of this study are to discover (i) the strategic plan at Youth and Sports Education Office and (ii) the formulation of education program at Youth and Sports Education Office in Enrekang district. The type of the study was descriptive qualitative research. The study was conducted at Youth and Sports Education Office in Enrekang district. Source of main data in the study were strategic plan of Enrekang district in 2009-2013, the head of Youth and Sports Education office, the secretary of Youth and Sports Education Office, and head department of planning